Proteostasis and ALS: protocol for a phase II, randomised, double-blind, placebo-controlled, multicentre clinical trial for colchicine in ALS (Co-ALS). Issue 5 (30th May 2019) - Mandrioli, Jessica; Crippa, Valeria; Cereda, Cristina; Bonetto, Valentina; Zucchi, Elisabetta; Gessani, Annalisa; Ceroni, Mauro; Chio, Adriano; D'Amico, Roberto; Monsurrò, Maria Rosaria; Riva, Nilo; Sabatelli, Mario; et al.
Abstract : Introduction: Disruptions of proteasome and autophagy systems are central events in amyotrophic lateral sclerosis (ALS) and support the urgent need to find therapeutic compounds targeting these processes. The heat shock protein B8 (HSPB8) recognises and promotes the autophagy-mediated removal of misfolded mutant SOD1 and TDP-43 fragments from ALS motor neurons (MNs), as well as aggregating species of dipeptides produced in C9ORF72-related diseases. In ALS-SOD1 mice and in human ALS autopsy specimens, HSPB8 is highly expressed in spinal cord MNs that survive at the end stage of disease. Moreover, the HSPB8–BAG3–HSP70 complex maintains granulostasis, which avoids conversion of dynamic stress granules (SGs) into aggregation-prone assemblies. We will perform a randomised clinical trial (RCT) with colchicine, which enhances the expression of HSPB8 and of several autophagy players, blocking TDP-43 accumulation and exerting crucial activities for MNs function. Methods and analysis: Colchicine in amyotrophic lateral sclerosis (Co-ALS) is a double-blind, placebo-controlled, multicentre, phase II RCT. ALS patients will be enrolled in three groups (placebo, colchicine 0.01 mg/day and colchicine 0.005 mg/day) of 18 subjects treated with riluzole; treatment will last 30 weeks, and follow-up will last 24 weeks. The primary aim is to assess whether colchicine decreases disease progression as measured by ALS Functional Rating Scale - Revised (ALSFRS-R) at baseline and at treatment end. Secondary aims include assessment of (1) safety and tolerability of Colchicine in patiets with ALS; (2) changes in cellular activity (autophagy, protein aggregation, and SG and exosome secretion) and in biomarkers of disease progression (neurofilaments); (3) survival and respiratory function and (4) quality of life. Preclinical studies with a full assessment of autophagy and neuroinflammation biomarkers in fibroblasts, peripheral blood mononuclear cells and lymphoblasts will be conducted in parallel with clinic assessment to optimise time and resources. Ethics and dissemination: The study protocol was approved by the Ethics Committee of Area Vasta Emilia Nord and by Agenzia Italiana del Farmaco (EUDRACT N.2017-004459-21) based on the Declaration of Helsinki. This research protocol was written without patient involvement. Patients' association will be involved in disseminating the study design and results. Results will be presented during scientific symposia or published in scientific journals. Trial registration number: EUDRACT 2017-004459-21; NCT03693781 ; Pre-results.